Zirconium Based Ion Exchangers as Catalysts in Esterification Reactions of Benzoic Acid - Singh, Charanjit; K. Mittal, Susheel; Kaur, Navneet (Asian Journal of Chemistry, 2015)
Zirconium based double salts were used as catalysts in esterification reactions of benzoic acid with some primary and secondary alcohols. Ester products were characterized with 1H NMR and FT-IR techniques. Product yields from different set of combinations of benzoic acid and alcohols were monitored using gas chromatography. Double salt based ion exchangers selectively catalyzed esterification reactions based on steric considerations. Electronic factor did not seem to play any role in efficiency of the inorganic ion exchangers as heterogeneous catalysts.